Diazole and triazole inhibition of nitrification process in return activated sludge. (February 2020) - Li, Guangbin; Field, James A.; Zeng, Chao; Madeira, Camila Leite; Nguyen, Chi Huynh; Jog, Kalyani Vikas; Speed, David; Sierra-Alvarez, Reyes
Abstract: Azoles are emerging contaminants that are resistant to biodegradation during wastewater treatment. Their presence has been widely reported in wastewater effluents and receiving waters. In this work, the potential inhibition of nitrification process by six different azole compounds in wastewater treatment plants was investigated in batch bioassays. The azoles studied included three diazoles: pyrazole (Pz); 1-methylpyrazole (MePz); 3, 5-dimethylpyrazole (DMePz); and three triazoles: 1, 2, 4-triazole (Tz); benzotriazole (BTz); and 5-methyl benzotriazole (MeBTz). The concentration of azoles causing 50% inhibition (IC50 ) increased (azoles became less inhibitory) in the following order (mg L −1 ): BTz (1.99) < MeBTz (2.18) < Pz (2.69) < Tz (3.53) < DMePz (17.3) < MePz (49.6). No clear structure-inhibitory relationships were found using Log P and pKa as structural properties. The toxicity of any given azole may be related to the role of substituent groups on disabling/enabling binding to the active sites of metallo-enzymes in nitrifying microorganisms. This is exemplified by the low toxicity of MePz, which has a cyclic N blocked by a methyl group. The observed inhibition caused to nitrifying bacteria is more severe than their cytotoxicity to other target organisms (e.g., methanogens and heterotrophic bacteria), suggesting a specific inhibition to the copper-containing enzyme, ammonium monooxygenase, in ammonia oxidizing nitrifying microorganisms. Graphical abstract: Image 1 Highlights: Six azoles were selected to test their inhibition effects on nitrification process. Nitrification is more sensitive to azoles than other microbial processes. Only a few mg L −1 of azoles can interfere with the nitrification process. The inhibition target is hypothesized to be ammonia monooxygenase. Steric hindrance may explain why 3, 5-demethylpyrazole is less toxic than other azoles.